Prevalence, pattern and determinants of urine abnormalities among school pupils in a semi-urban community - Kolawole Alaje; Tamramat RUnsewe-Abiodun; Olatubosun Olawale (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: Dipstick urinalysis is a semi-quantitative examination of the urine, which can be utilized as a screening and diagnostic tool in children. It is rapid, sensitive, easy to perform and affordable for the resource-poor environment. Objectives: To describe the pattern of urinalysis findings using urinary dipsticks and the determinants of urine abnormality among pupils in primary schools in a semi-urban area. Methods: Apparently healthy 387 pupils were recruited from 10 public and 5 private primary schools in Ikenne Local Government Area of Ogun State, Nigeria using multi-stage and proportionate sampling techniques. Data on demography, nutritional status and urinary examination were obtained using Interviewer-administered questionnaires, clinical examination and dipstick urinalysis respectively. Results: Dipstick urinalysis revealed the following; urine pH and specific gravity were normal in 98.2% and 100.0% of the pupils respectively. Protein, leukocyte esterase, nitrite, bilirubin, urobilinogen, blood and ketones were detected in 18.1%, 15.8%, 14.2%, 3.3%, 2.1%, 0.8%, and 0.5% respectively. Glucose and ascorbic acid were generally absent in the urine samples. Female gender significantly contributed to the pattern of urinalysis (leukocyte esterase and nitrites). Proteinuria was most frequent among the underweight (38/70; 54.3%). Urine abnormalities were more prevalent among pupils in public schools compared with private schools though not statistically significant, and not influenced by gender. Conclusion: Asymptomatic proteinuria and urinary tract infection are not uncommon among children. Female gender and socio-economic status play a role in the incidence of the conditions.